Managing Learning for Quality Improvement (Mengelola Pembelajaran untuk Peningkatan Mutu) - Muzakki, Hawwin (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2015)
Quality education needed in order to prepare high Â quality human resource, in the sense of science, a skill (lifeskill) , and possession technology. The efforts to improve and Â improve the Â quality of education like never stopped. Many reform agenda that, while, and will be implemented. Reforming education not just enough Â to change in the curriculum , but should be followed by change study practice and Â learning on and off Â class. Change tradition lessons learned student centered to excel instantly toward (learned to learn) or (learn to realize learn)Â was indeed not easy. For this very essential to formulate how to manage learning that students can learn how to learn, which finally ended up at developing and improving the quality of learning